Displaced Acetabular Fracture in Elderly Patients: Is Acute Arthroplasty an Effective Option? - Yang, Zhengming; Röhrl, Stephan Maximillian; Nordsletten, Lars (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background and study aim Elderly individuals are the most rapidly growing subgroup of patients currently sustaining acetabular fractures, and total hip arthroplasty (THA) is being applied more and more in the treatment of acetabular fractures. The purpose of this study was to review the available literature regarding displaced acetabular fractures in elderly patients treated with acute THA.Study design A search was conducted using the electronic databases Medline, PubMed, ISI Web of Knowledge, and Scopus on papers published between January 1960 and November 2018 using the terms “acetabular fracture” plus “elderly patients” plus “arthroplasty”. A systematic review of the literature on the different treatment options for acute THA is presented.Results The search yielded a total of 320 articles, and 9 articles were selected for review. The indications, techniques, approaches, and complications of THA are discussed, and a treatment recommendation based on the selected articles is given.Conclusion We consider acute arthroplasty an effective treatment option for displaced acetabular fractures in elderly patients, while different techniques should be used for different displaced acetabular fractures in this patient group.
Keywords: displaced acetabular fractures; acute total hip arthroplasty; elder patients; systematic review